2020
DOI: 10.1097/bot.0000000000001687
|View full text |Cite
|
Sign up to set email alerts
|

Reamed Versus Unreamed Intertrochanteric Femur Fractures, Is It Time?

Abstract: Objectives: This study compares the intraoperative and postoperative outcomes of the traditional technique of femoral canal reaming to placement of an unreamed 10-mm nail. Design: Retrospective cohort study. Setting: Academic Level I Trauma Center, Southeastern US. Patients/Participants: Intertrochanteric femur fractures treated with a CMN (January 2016–December … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…In earlier studies in geriatric patients, no significant differences in blood loss, the need of transfusion or haemoglobin/haematocrit were detected between reamed and unreamed femoral fractures. While a significant shorter duration of operation was needed in the unreamed group, both techniques showed satisfactory results in stabilization 29 . In addition, treatment with RIA I showed a relevant blood loss in 3.22% of patients, which needed transfusion 30 .…”
Section: Discussionmentioning
confidence: 86%
“…In earlier studies in geriatric patients, no significant differences in blood loss, the need of transfusion or haemoglobin/haematocrit were detected between reamed and unreamed femoral fractures. While a significant shorter duration of operation was needed in the unreamed group, both techniques showed satisfactory results in stabilization 29 . In addition, treatment with RIA I showed a relevant blood loss in 3.22% of patients, which needed transfusion 30 .…”
Section: Discussionmentioning
confidence: 86%
“…[ 24 ] The use of 10 mm diameter nails has also obviated the need for reaming the canal in trochanteric fractures, with no significant difference in perioperative and postoperative outcomes compared with reamed nailing in 37 patients. [ 25 ] There were no cases of anterior cortical penetration in the unreamed group. [ 25 ]…”
Section: Discussionmentioning
confidence: 99%
“…A recent retrospective study showed 10 mm nails to be of adequate strength, regardless of femoral canal length, to promote healing in 147 patients with femoral shaft fractures [24] . The use of 10 mm diameter nails has also obviated the need for reaming the canal in trochanteric fractures, with no significant difference in perioperative and postoperative outcomes compared with reamed nailing in 37 patients [25] . There were no cases of anterior cortical penetration in the unreamed group [25] …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The specific surgical risk associated with reaming in unilateral hip fracture in the elderly has been mentioned recently in the literature. Pitts et al, 36 in a retrospective comparative study of 65 elderly patients with hip fractures, reported shorter operative time for the nonreamed group (16 min on average), without other significant differences in intraoperative blood loss, trans-fusion requirements, hospital stay, failure of osteosynthesis, postoperative complications, and death. In the authors' experience with patients sustaining bilateral hip fractures, they usually ream the femur treated with a long nail to decrease the risk of intraoperative fracture, and they treat the contralateral fracture with a short nonreamed nail to minimize the risks associated with a bilateral reaming procedure.…”
Section: Type Of Implant and Other Technical Considerationsmentioning
confidence: 99%